The effect of dietary level of two inulin types differing in chain length on biogenic amine concentration, oxidant-antioxidant balance and DNA repair in the colon of piglets - Barszcz, Marcin (PLoS One, 2018)
The effect of dietary level of two types of inulin on amine concentration, redox status and DNA glycosylase activity in the colon of piglets was investigated. Seven groups of piglets were fed diets without inulin addition (control) or with 1%, 2% or 3% inulin with an average degree of polymerisation of 10 (IN10) or 23 (IN23) for 40 days. The 2% and 3% IN10 diets increased tryptamine concentration in the proximal colon, while methylamine concentration in the distal colon was increased by the 1% and 3% IN10 diets. The 1% and 2% IN23 diets increased phenylethylamine and methylamine concentration in the proximal colon, respectively, while 1,7-diaminoheptane content was increased by both diets. Its concentration in the middle and distal colon was increased by the 1% and 2% IN23 diet, respectively. There was no improvement in the oxidant-antioxidant balance in colonic digesta of piglets fed IN10 and IN23 diets. Piglets fed IN10 diets had lower 1,N(6)-etheno-2’-deoxyadenosine excision activity in each colon segment, as compared with the control group. It was also reduced by the 2% and 3% IN23 diets in the proximal colon, while in the middle and distal colon by all IN23 diets. Feeding all IN10 and IN23 diets reduced 3,N(4)-etheno-2’-deoxycytidine and 8-oxo-deoxyguanosine excision activities in each colon segment. Feeding IN10 and IN23 diets neither decreased amine concentrations nor improved the oxidant-antioxidant balance in colonic digesta of piglets. However, both types of inulin efficiently reduced the activity of DNA repair enzymes.